THE EFFECT OF EMPLOYEES EMOTIONAL INTELLIGENCE ON THE BEHAVIOR OF CUSTOMER SERVICE AND EMPLOYEE PERFORMANCE OF BANK MUAMALAT TASIKMALAYA BRANCH - Endang Syarif; Rian Apriatna (JARES (Journal of Academic Research and Sciences), 2018)
This study analyzed the emotional intelligence (EQ) that occurred in the branch of Bank Muamalat Tasikmalaya associated with the behavior and performance of employees serving customers, with the number of respondents reached 68 people. The test is done by using simple linear regression with devenden variable (Y1) serving and Behavior (Y2) performance, where the indevendent variable (X) is emotional intelligence (EQ) in self-awareness identification, self-regulation, motivation, empathy and social skill. From the result of research found that emotional intelligence (EQ) have significant effect to service behavior 48,5% and influence to employee performance equal to 39,7% significantly. The influence of t count value from 7,886 to model the influence of emotional intelligence on the service behavior and t count 6,587 to model the influence of emotional intelligence on performance and tested at Î± = 5% and prove the independent variable which influenced on the dependent variable, while regression analysis showed as 10,257 constants the results for the behavioral model of the influence of emotional intelligence function, and the constant of 9,553 for the model of the influence of emotional intelligence on performance, the results of this test explains that emotional intelligence (EQ) in employee roles improves the behavior and performance of Bank employees serving the branch Muamalat Tasikmalaya.